Enhancing vaccine half-life as a novel strategy for improving immune response durability of subunit vaccines. - Zhaoling Shen; Cheng Li; Wenping Song; Litong Liu; Yu Kong; Ailing Huang; Qingui Bao; Tianlei Ying; Yanling Wu (PLoS Pathogens)
Vaccines are widely regarded as one of the most effective strategies for combating infectious diseases. However, significant challenges remain, such as insufficient antibody levels, limited protection against rapidly evolving variants, and poor immune durability, particularly in subunit vaccines, likely due to their short in vivo exposure. Recent advances in extending the half-life of protein therapeutics have shown promise in improving drug efficacy, yet whether increasing in vivo persistence can enhance the efficacy of subunit vaccines remains underexplored. In this study, we developed two trimeric SARS-CoV-2 subunit vaccines with distinct pharmacokinetic profiles to evaluate the impact of vaccine persistence on immune efficacy. A self-assembling trimeric subunit vaccine (RBD-HR/trimer) was designed, followed by an extended-persistence variant (RBD-sFc-HR/trimer) incorporating a soluble monomeric IgG1 fragment crystallizable. We demonstrated that RBD-sFc-HR/trimer elicited more robust and higher levels of neutralizing antibodies, with potent and broad neutralization activity against multiple SARS-CoV-2 variants. Notably, RBD-sFc-HR/trimer induced a durable immune response, significantly increasing the number of memory B cells and T cells. This study provides critical insights for designing vaccines that achieve potent and long-lasting immune responses against infectious diseases.